2007
DOI: 10.1007/s00432-006-0186-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of aromatase protein expression in axillary node negative breast cancer

Abstract: Our study suggested that local estrogen production by aromatase plays important roles in the growth and invasiveness of breast cancer; tumor aromatase status may be indicative of breast cancer prognosis in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Di et al When we evaluated only IDC we found a statistically significant positive correlation between aromatase and MMP-2 (p=0.001) and between aromatase and MMP-9 (p=0.034). Similar results were obtained by Di et al (2005) and Lu et al (2007) with p<0.001 21,22 . These results and others that show positive correlation between aromatase and MMP-2 and aromatase and MMP-9 increase the possibility that aromatase can elevate the invasion capacity of tumor cells by increasing the activity of MMP-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Di et al When we evaluated only IDC we found a statistically significant positive correlation between aromatase and MMP-2 (p=0.001) and between aromatase and MMP-9 (p=0.034). Similar results were obtained by Di et al (2005) and Lu et al (2007) with p<0.001 21,22 . These results and others that show positive correlation between aromatase and MMP-2 and aromatase and MMP-9 increase the possibility that aromatase can elevate the invasion capacity of tumor cells by increasing the activity of MMP-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 90%
“…Eppenberger et al (2001) 39 found that women with high aromatase expression in breast cancer have increased 22 in the univariate survival analysis showed that aromatase is significantly and positively associated with decreased overall survival (OS) (p= 0.04) in the estrogen receptor (ER) and/or progesterone receptor (PR), positive patients (10 year OS 100% for the aromatasenegative group compared with 85.1% for the aromatase-positive group). However, in the multivariate survival analysis, we did not find this association to be significant (p> 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is supported by activity studies showing a higher enzyme activity of aromatase in the stroma [23,43]. Several investigations of aromatase protein expression and its correlation to patient outcome have been carried out without discriminating between stromal and epithelial localisation [32,33,44], which generate difficulties in comparing results between studies. We also measured the mRNA levels of sulfatase and aromatase and did not find any significant correlation between mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 87%
“…The majority of ER α -positive cells retain their ER α and respond positively to initial endocrine therapy for the treatment of advanced metastatic disease. Several recent studies have detected the presence of ER α expression in metastatic tumors [4648]. A correlation between ER α -positive tumors and the development of bone metastasis has been observed clinically [49, 50].…”
Section: Erα Regulation Of Metastasismentioning
confidence: 99%